Clinico-Mycological Profile of Dermatophytosis in a Tertiary Care Hospital in North India (Indian Journal of Public Health Research & Development, 2020)
Introduction: - Dermatophytosiscomprise approximately 15- 75% of all the mycological infections. It is common in tropical and subtropical countries including India where high temperature and humidity play an important role in the pathogenesis. Dermatophytes are closely related keratinolytic fungi with the ability to degrade keratin and invade the skin, hair and nails causing dermatophytosis. Objective: - To find out the distribution of various dermatophytefungi responsible for the different clinical types of dermatophyte infections. Methods: - KOH mount were prepared from the skin scrapings, nail clippings, and hair bits to look for fungal elements. The specimens were also inoculated on Mycosal media and Sabourauds dextrose agar with chloramphenicol. The dermatophytes were identified on the basis of colony characteristics, lactophenol cotton blue mount, nutritional requirement, temperature tolerance, urease production, and in vitro hair perforation test. Result: - A total of 245 patients were included in the study. Tinea corporis was most common clinical type with 102(41.6%) cases followed by T. facei[15 (6.1%)]. T. corporis +T. cruris [88(35.9%)] was most common mixed clinical type. Out of 245 patients, fungal hyphae were seen in 162(66.1%) samples and the rest 83(33.9%) were negative by KOH mount. In the 162 KOH positive samples, 151(91.5%) samples were culture positive and 11(13.7%) were culture negative. In 83(58.9%) KOH negative samples, 14(8.5%) were culture positive and rest 69(86.3%) were culture negative. A total of 165 samples were culture positive, of which T. mentagraphyteswas isolated in 153(92.7%) followed by T. rubrum in 5(3.03%), T. violaceum in 3(1.8%), T.tonsurans in 2(1.2%) and M.canis in 2(1.2%) samples.
Keywords: Dermatophytosis, Fungal Culture, Mycosal media, Taenia corporis, Trichophyton, Microsporum